From Shakespeare to Drzic and Back: A Reassessment - Čale Feldman, Lada (2004)
The paper deals with the already acknowledged coincidences between the opus of the Renaissance playwright Marin Držić and William Shakespeare's comedies, while trying to suggest new questions and propose new avenues for comparison.